2015
DOI: 10.1073/pnas.1417059112
|View full text |Cite
|
Sign up to set email alerts
|

Saccade direction encoding in the primate entorhinal cortex during visual exploration

Abstract: We recently demonstrated that position in visual space is represented by grid cells in the primate entorhinal cortex (EC), suggesting that visual exploration of complex scenes in primates may employ signaling mechanisms similar to those used during exploration of physical space via movement in rodents. Here, we describe a group of saccade direction (SD) cells that encode eye movement information in the monkey EC during free-viewing of complex images. Significant saccade direction encoding was found in 20% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 51 publications
11
65
0
Order By: Relevance
“…Congruent with a neural spatial map of where the a primate is looking, entorhinal cells have been identified that provide a grid-like representation of fixation locations on a computer monitor as monkeys freely viewed images (Killian et al, 2012; Meister et al). In addition, similar to heading direction cells in rodents (Taube, Muller, and Ranck, 1990), entorhinal neurons were recently found to be selective for the direction of the upcoming or previously-completed saccade regardless of where the monkey was currently looking (Killian et al, 2015). Although the details regarding these different reference frames across species and brain structures remain to be resolved, a more central remaining mystery is how MTL neurons with spatial representation potentially influence orienting behavior guided by memory.…”
Section: Why Study the Neurophysiology Of Memory Through Eye Movemmentioning
confidence: 94%
See 1 more Smart Citation
“…Congruent with a neural spatial map of where the a primate is looking, entorhinal cells have been identified that provide a grid-like representation of fixation locations on a computer monitor as monkeys freely viewed images (Killian et al, 2012; Meister et al). In addition, similar to heading direction cells in rodents (Taube, Muller, and Ranck, 1990), entorhinal neurons were recently found to be selective for the direction of the upcoming or previously-completed saccade regardless of where the monkey was currently looking (Killian et al, 2015). Although the details regarding these different reference frames across species and brain structures remain to be resolved, a more central remaining mystery is how MTL neurons with spatial representation potentially influence orienting behavior guided by memory.…”
Section: Why Study the Neurophysiology Of Memory Through Eye Movemmentioning
confidence: 94%
“…By recording and stimulating in two brain structures at different time points relative to an eye movement, MTL connectivity with the inferotemporal cortex, known for visual object processing, was shown to peak 100 ms after fixation even for saccades made in darkness (Sobotka, Zuo, and Ringo, 2002). Additionally, neurons coding for the direction of a saccade have recently been reported in the entorhinal cortex (Killian, Potter, and Buffalo, 2015). Taken together, these findings demonstrate the relevance of eye movement itself to MTL processing.…”
Section: Why Study the Neurophysiology Of Memory Through Eye Movemmentioning
confidence: 99%
“…Despite the overall similarity between the anatomies of the rat and human EC, primate data suggest that the human EC receives a larger contribution from higher visual cortical areas (25). In primates, behavior as restricted as eye movements over static visual displays is sufficient to elicit spatially periodic ("grid-like") patterns of neuronal activity that correlate with saccade direction (26,27). Interspecies differences in sensory processing make the spatial representations of place cells display marked variability.…”
Section: Significancementioning
confidence: 99%
“…Research regarding the functional significance of the distinct regions of the ERC in human and non-human primates is just emerging; however, in primates, cells in posterior ERC code for saccade direction during visual exploration (Killian, Potter, Buffalo, 2015).…”
Section: Cc-by-nc-ndmentioning
confidence: 99%